2007
DOI: 10.1001/jama.297.13.1435
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Influenza B Viruses With Reduced Sensitivity to Neuraminidase Inhibitors

Abstract: In this population, influenza B viruses with reduced sensitivity to neuraminidase inhibitors do not arise as frequently as resistant influenza A viruses. However, they appear to be transmitted within communities and families, requiring continued close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 25 publications
10
162
1
1
Order By: Relevance
“…Oseltamvir is an oral drug, whereas zanamivir is inhaled; therefore, oseltamivir is the more extensively used. Although the prevalence of viruses resistant to these drugs is lower than that for the aminoadamantanes (7,8), a higher proportion of oseltamivir-resistant viruses has been detected among treated patients than was expected (9), and person-to-person transmission of oseltamivir-resistant influenza B viruses has occurred (10). Furthermore, oseltamivirresistant H1N1 viruses emerged during the 2007-2008 season (11), and currently most H1N1 viruses are oseltamivir-resistant (12,13).…”
mentioning
confidence: 99%
“…Oseltamvir is an oral drug, whereas zanamivir is inhaled; therefore, oseltamivir is the more extensively used. Although the prevalence of viruses resistant to these drugs is lower than that for the aminoadamantanes (7,8), a higher proportion of oseltamivir-resistant viruses has been detected among treated patients than was expected (9), and person-to-person transmission of oseltamivir-resistant influenza B viruses has occurred (10). Furthermore, oseltamivirresistant H1N1 viruses emerged during the 2007-2008 season (11), and currently most H1N1 viruses are oseltamivir-resistant (12,13).…”
mentioning
confidence: 99%
“…Both isolates were collected from SARI patients without historical drug exposure. A few previous studies have revealed influenza B virus with reduced susceptibility to NAIs, particularly oseltamivir (2,21,22). As indicated by substantially higher oseltamivir IC50 values, influenza B viruses appear to be more sensitive to zanamivir than oseltamivir.…”
Section: Discussionmentioning
confidence: 96%
“…CDC continues to recommend that adamantane drugs not be used for infl uenza treatment in the United States. Given the recent emergence of oseltamivir-resistant infl uenza A and B infections (15,16), ongoing monitoring of infl uenza virus susceptibility to adamantanes and neuraminidase inhibitors is essential.…”
Section: Discussionmentioning
confidence: 99%